2014
DOI: 10.1007/s10900-014-9856-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Social Determinants of Youth Physical Activity Intensity Levels at Neighborhood Parks in Las Vegas, NV

Abstract: Parks can play an important role in youth activity. This study used observational data to evaluate the relationship of environmental and social determinants to youth physical activity intensity levels in Las Vegas neighborhood parks. System for observing play and leisure activity in youth was used to code activity levels as sedentary, walking, or vigorous in five low-income and five high-income parks. Environmental determinants included amenities, incivilities, size, high-speed streets, sidewalk condition, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…Methods used in the current study precluded assessment of relationships among children. The findings are nevertheless consistent with studies that show friendships among adolescents are strong predictors of their physical activity levels (9). Presence of parents was associated with a lower likelihood of increased activity among children and adolescents with a stronger negative trend observed among girls.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Methods used in the current study precluded assessment of relationships among children. The findings are nevertheless consistent with studies that show friendships among adolescents are strong predictors of their physical activity levels (9). Presence of parents was associated with a lower likelihood of increased activity among children and adolescents with a stronger negative trend observed among girls.…”
Section: Discussionsupporting
confidence: 90%
“…Interventions can target multiple scales (ie, neighborhoods, parks, and areas within parks). In light of data from earlier studies (69), these findings suggest that activity areas within parks can be the focus of environmental or policy change.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The earliest study initiated observations in 2003 (McKenzie et al, 2006), when the SOPARC method was created, and the latest study started observations in 2013 (Roemmich and Johnson, 2014). While all studies employed SOPARC observational techniques, two studies referred to using SOPLAY (an earlier version of SOPARC) (Coughenour et al, 2014; Floyd et al, 2008a). …”
Section: Resultsmentioning
confidence: 99%
“…In terms of park users, one study reported observing adults only (Reed et al, 2008) and two reported observing youths only (Coughenour et al, 2014; Floyd et al, 2011; Reed and Hooker, 2012). Several other studies modified the age categories by combining teenagers with adults (< = 12 years and > = 13 years) (Chung-Do et al, 2011; Floyd et al, 2008a) and two studies combined all youths, not distinguishing younger and older youths (Child et al, 2014; McCormack et al, 2014).…”
Section: Resultsmentioning
confidence: 99%